Pengaruh Budaya Organisasi, Kompetensi Dan Pengembangan Karir Terhadap Kepuasan Kerja Pegawai Pada Sekretariat Daerah Pusat Pemerintahan Kota Tangerang - Azzahra, Wardhatul Jannah; Maswanto, Maswanto (Jurnal Ekonomika Dan Bisnis (JEBS), 2025)
Job satisfaction refers to the feeling of achievement or satisfaction that a person feels when carrying out their work. This study aims to determine the Influence of Organizational Culture, Competence and Career Development on Employee Job Satisfaction at the Central Regional Secretariat of the Tangerang City Government. The number of population and sample in this study amounted to 70 employees using a saturated sample. The research method used is a quantitative method that is associative using primary data. The data analysis technique used is multiple linear regression analysis. Based on the results of the research, it can be seen that organizational culture has a positive and significant effect on employee job satisfaction, competence has a positive and significant effect on employee job satisfaction and career development has a positive and significant effect on employee job satisfaction. In addition, it can be seen that organizational culture, competence and career development together have a positive and significant effect on employee job satisfaction. Based on the results of the determination coefficient test, the R Square was obtained at 0.726 or 72.6%, meaning that the influence of organizational culture, competence and career development on employee job satisfaction was 72.6%, while the remaining 27.4% was influenced by other variables that were not included in this study.